The Economy Of Francesco And The Macau Institute: A Double Manifesto For Gratuitousness And Virtue Ethics In Economics (The Macau Ricci Institute Journal, 2023)
November 2020 saw the elaboration and publication of two important documents: the Final Statement (2020) of the young participants in the Economy of Francesco (EoF) and the Macau Manifesto (2020) written by participants in the Macau Ricci Institute Symposium at the University of Saint Joseph. These two research groups converge on many substantial points and, most significantly, on a common methodological understanding: rather than reforming or revolutionising the current economic system, it is necessary to transform it. This means not destroying and changing all its principles, nor accepting them all, but rather adding what is missing from the current picture. What is it that is missing? Both the EoF and the Macau Manifesto understand that a reconsideration of the economy as a practice directed toward virtue and common good is needed.